The trumpeter of Krakow, - Kelly, Eric P. (Eric Philbrook), 1884-1960 (Collier Books, 1973)
A Polish family in the Middle Ages guards a great secret treasure and a boy's memory of an earlier trumpeter of Krakow makes it possible for him to save his father.